Dispositivos de armazenamento de energia aquosos utilizando nanoestruturas de carbono e hexacianoferratos de zircônio e vanádio como catodo - Silva, Samuel Carlos (2025)
This work proposed fully chemical synthetic routes to produce nanocomposite powders of zirconium hexacyanoferrate (ZrHCF) and vanadium hexacyanoferrate (VHCF) with graphene oxide (GO) and functionalized carbon nanotubes (CNT). Graphene oxide was obtained through chemical exfoliation of graphite with strong oxidants. Carbon nanotubes were functionalized through ultrasonic sonication in acid solutions. Each hexacyanoferrate was prepared through coprecipitation using controlled addition of precursor solutions in reactional media containing previous dispersed carbon nanostructures. Diffractometric data confirmed the formation of an amorphous phase of ZrHCF, and face centered cubic structure of VHCF. Spectroscopic data confirmed the presence of both metallic hexacyanoferrates and carbon nanostructures in the powders, in addition to elemental composition and oxidation states of VHCF. Scanning and transmission electron microscopy images demonstrated the contact between carbon nanostructures and synthesized hexacyanoferrates. ZrHCF powder was employed in a 3-electrode electrochemical cell with graphene current collectors. This cell underwent cyclic voltametric and galvanostatic charge discharge experiments in a H2SO4 electrolyte with factorial design defined concentration, aiming to highlight the potential of ZrHCF cathodes as aqueous proton batteries. The cathode exhibited 100 mAh g-1 specific capacity and an average potential of 0,3 V. VHCF powders were evaluated in concentrated ZnCl2 electrolytes with metallic Zn anode in 2 and 3-electrode cells. Results presented excellent specific capacity, when compared to other HCF, up to 230 mAh g-1, 1,0 V of average potential and 86% capacity retention in 1000 cycles, with different surface phenomena being studied through different characterization techniques, with untapped chlorine hosting in the VHCF cathode being demonstrated for the first time. Pouch cell testing was conducted to display the commercial potential of the device. GO/VHCF nanocomposite presented 200 mAh g-1 specific capacity in only 20 cycles, indicating the promising performance of the proposed nanocomposite powders.